Sports Analytics - Alceo, Pedro (2019)
Alceo, P., & Henriques, R. (2019). Sports Analytics: maximizing precision in predicting MLB base hits. In A. Fred, & J. Filipe (Eds.), Proceedings of the 11th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management (IC3K 2019) (pp. 190-201). (IC3K 2019 - Proceedings of the 11th International Joint Conference on Knowledge Discovery, Knowledge Engineering and Knowledge Management; Vol. 1). SciTePress. https://doi.org/10.5220/0008362201900201